Louise Blanchard Bethune : Every Woman Her Own Architect. - Hayes McAlonie, Kelly (Albany : State University of New York Press, 2023)
The trailblazing story of the life and career of Louise Blanchard Bethune, America's first professional woman architect.
Cover -- Title Page -- Copyright -- Dedication -- Contents -- List of Illustrations -- Acknowledgments -- Abbreviations -- Introduction -- Chapter 1. Becoming Louise: Early Life, Family, Education, and Apprenticeship -- Chapter 2. Family and Firm -- Chapter 3. Home Work: Women as Architects -- Chapter 4. Welcome to the Club -- Chapter 5. The Architecture of Education -- Chapter 6. Innovation, Industry, and Entertaining the Public: 1888-1900 -- Chapter 7. Riding into the Future: The Wheelwoman and Feminist -- Chapter 8. A Question of Equality: The Woman's Building -- Chapter 9. The Triumphant Hotel Lafayette-and Beyond -- Conclusion: The Forgotten Woman Architect-Rediscovered -- Appendix Bethune, Bethune &amp -- Fuchs Buildings -- Notes -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books